PENGGUNAAN DESIGN THINKING DALAM PENGEMBANGAN PRODUK KERAJINAN IKM (Studi Kasus: Sentra Kerajinan Patung Kayu, Subang) - Noel Febry Ardian; Hendriana Werdhaningsih (Universitas Trisakti, 2018)
Collaboration between craftsmen and product designers is one of the solutions for sustainable development of IKM products. Craftsmen need to be introduced to the creative process in producing new products. One that can be applied is Design Thinking. This process is considered in accordance with the way the craftsman works which generally